2017
DOI: 10.1159/000484329
|View full text |Cite
|
Sign up to set email alerts
|

AF1q Contributes to Adriamycin-Induced Podocyte Injury by Activating Wnt/β-Catenin Signaling

Abstract: Background/Aims: Injury of podocytes plays an important role in decline of glomerular filtration and proteinuria. It is well-known that proteinuria is associated with numerous chronic kidney diseases (CKD). However, the underlying mechanism of podocyte injury remains unclear. Methods: We used reverse transcription-quantitative PCR (RT-qPCR) to compare the expression level of the ALL1-fused from the chromosome 1q (AF1q) gene in mice and mouse podocytes (MPC5) with or without Adriamycin (ADR) treatment. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Podocytes play a key role in glomerular selective filtration function [10, 11]. Podocyte dysfunction or injury induced by various stresses and pathological stimuli is thought to be critical for the pathogenesis of proteinuria and glomerular diseases [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Podocytes play a key role in glomerular selective filtration function [10, 11]. Podocyte dysfunction or injury induced by various stresses and pathological stimuli is thought to be critical for the pathogenesis of proteinuria and glomerular diseases [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…ADR-induced nephrotic mouse model characterized by podocyte injury, glomerulosclerosis and tubulointerstitial inflammation (13). However, due to high accumulation in the kidney, it causes severe nephrotoxicity, such as elevated serum creatinine and proteinuria levels (13,14). In the present study, we continued to investigate STAT1-p53-p21axis involved in the development of adriamycin (ADR)-induced CN in a classical mouse model.…”
Section: Introductionmentioning
confidence: 93%
“…ADR shows the toxicity to podocytes, which might be resulted in the renal inflammation (134). Podocytes are highly specialized cells maintaining the glomerular filtration barrier, and podocyte injury is observed in various renal diseases (3334).…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes are highly specialized cells maintaining the glomerular filtration barrier, and podocyte injury is observed in various renal diseases (3334). Several studies showed that MSCs inhibited podocyte apoptosis via epithelial growth factor, VEGF, CCAAT/enhancer binding protein-α, and β-catenin in ADR-induced and a diabetic nephropathy (3434). Consistently, our data demonstrate that MSCs significantly decrease the expression of the podocyte injury marker desmin in the kidney of ADR-treated mice and significantly inhibit pro-apoptotic BAX expression in ADR-treated podocytes in an in vitro co-culture setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation